THE NUMERICAL MODEL OF THE BUILDING VENTILATION DURING THE EMERGENCY RELEASES OF HAZARDOUS SUBSTANCES - Zaiats, Yu. L.; Beliaeva, V. V. (Science and Transport Progress, 2005)
A numerical model to simulate the process of pollutant transfer in rooms was developed. The numerical simulation is carried out using 2D models of pollutant transfer and potential flow. The implicit finite difference schemes are used. The results of numerical simulation of air pollution in a confined space after blasts of toxic substances have presented.